Proton and hydrogen transport through two-dimensional monolayers. (30th March 2016) - Seel, Max; Pandey, Ravindra
Abstract: Diffusion of protons and hydrogen atoms in representative two-dimensional materials is investigated. Specifically, density functional calculations were performed on graphene, hexagonal boron nitride (h-BN), phosphorene, silicene, and molybdenum disulfide (MoS2 ) monolayers to study the surface interaction and penetration barriers for protons and hydrogen atoms employing finite cluster models. The calculated barrier heights correlate approximately with the size of the opening formed by the three-fold open sites in the monolayers considered. They range from 1.56 eV (proton) and 4.61 eV (H) for graphene to 0.12 eV (proton) and 0.20 eV (H) for silicene. The results indicate that only graphene and h-BN monolayers have the potential for membranes with high selective permeability. The MoS2 monolayer behaves differently: protons and H atoms become trapped between the outer S layers in the Mo plane in a well with a depth of 1.56 eV (proton) and 1.5 eV (H atom), possibly explaining why no proton transport was detected, suggesting MoS2 as a hydrogen storage material instead. For graphene and h-BN, off-center proton penetration reduces the barrier to 1.38 eV for graphene and 0.11 eV for h-BN. Furthermore, Pt acting as a substrate was found to have a negligible effect on the barrier height. In defective graphene, the smallest barrier for proton diffusion (1.05 eV) is found for an oxygen-terminated defect. Therefore, it seems more likely that thermal protons can penetrate a monolayer of h-BN but not graphene and defects are necessary to facilitate the proton transport in graphene.